Regional inequalities and the urban industrial agglomeration: case study Baghdad, Anbar, Diala, Wast and Babylon. - Hamem, Hassan J. (2008)
This paper examines the impact of industrial agglomeration in the city of Baghdad, and in particular the trend of regional inequalities rates, between Baghdad and surrounding cities. To determine rates of change in regional inequalities. Is it increasing or decreasing? And to determine of cities that are the inequalities between them and Baghdad more than others. There is more than one method to calculate the regional inequality, but the more popular; Williamson method, namely weighted coefficient of variation (Vw), but the key indicators were Indicators spatial, indicators of industrial activity in study areas only. Are not used general indicators, just like Williamson used. The general trend of the changes was increasing of regional inequalities, but the most prominent of regional inequalities was the largest share of the cities closest to Baghdad.